2019
DOI: 10.1007/s40279-019-01052-6
|View full text |Cite
|
Sign up to set email alerts
|

Revised Approach to the Role of Fatigue in Anterior Cruciate Ligament Injury Prevention: A Systematic Review with Meta-Analyses

Abstract: BackgroundCauses of anterior cruciate ligament (ACL) injuries are multifactorial. Anterior cruciate ligament injury prevention should thus be approached from a multifactorial perspective as well. Training to resist fatigue is an underestimated aspect of prevention programs given that the presence of fatigue may play a crucial role in sustaining an ACL injury.ObjectivesThe primary objective of this literature review was to summarize research findings relating to the kinematic and kinetic effects of fatigue on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 112 publications
(214 reference statements)
1
86
0
2
Order By: Relevance
“…Numerous studies have tested the effects of a single actual or simulated soccer match on markers of physical performance, including repeated sprint ability, vertical jump, and maximum voluntary leg strength, and almost all have found consistent effects of fatigue lasting as long as 48–72 h post-match [8,9]. However, several recent reviews point out that the kinematic and kinetic risk factors for non-contact ACL injury are not consistently present after a single bout of fatiguing exercise [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have tested the effects of a single actual or simulated soccer match on markers of physical performance, including repeated sprint ability, vertical jump, and maximum voluntary leg strength, and almost all have found consistent effects of fatigue lasting as long as 48–72 h post-match [8,9]. However, several recent reviews point out that the kinematic and kinetic risk factors for non-contact ACL injury are not consistently present after a single bout of fatiguing exercise [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, especially in women's singles matches played between higher-ranked players, more attention should be paid in the preparation of the players to prevent injury. Benjaminse et al (2019) suggested that training to resist fatigue could be effective for injury prevention as fatigue may play a crucial role in sustaining an ACL injury [20].…”
Section: Discussionmentioning
confidence: 99%
“…Their approach includes physiological and psychological processes, but fatigue is only regarded as a general phenomenon and not divided into subcategories, e.g., central or peripheral fatigue. Benjaminse et al [43] also describe fatigue as a complex interaction between psychological and physical factors. This interaction might influence the reactions to external stimuli and the decisions of an athlete in complex situations, e.g., landing or cutting in high-risk sports.…”
Section: Loading Protocolsmentioning
confidence: 99%